2018
DOI: 10.2298/vsp160616339p
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with chronic liver disease

Abstract: Background/Aim. Quality of life is impaired in patients with the chronic liver disease (CLD). Patients with this disease have numerous disabling problems which lead to a reduced health related quality of life (HRQoL). The aim of our study was to evaluate the predictive value of selected socio-demographic and clinical characteristics on HRQoL in Serbian cohort of patients with the CLD. Methods. Over a period of one year, we performed a study which included patients with the CLD. We used Short Form Health Survay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(111 reference statements)
3
0
0
Order By: Relevance
“…All symptom domains in our patient group had significant influence on patients' QoL. Fatigue was the symptom with the most prominent influence on HRQoL, which is similar to the findings of previously reported studies [4,21]. Fatigue has a major impact on PBC patients' QoL and has been associated with sleep disturbance among these patients, as well as autonomic dysfunction [18].…”
Section: Discussionsupporting
confidence: 89%
“…All symptom domains in our patient group had significant influence on patients' QoL. Fatigue was the symptom with the most prominent influence on HRQoL, which is similar to the findings of previously reported studies [4,21]. Fatigue has a major impact on PBC patients' QoL and has been associated with sleep disturbance among these patients, as well as autonomic dysfunction [18].…”
Section: Discussionsupporting
confidence: 89%
“…These findings were in line with research done in China by Alavinejad et al (20) , who discovered that more than two thirds of caregivers had a low QoL. Additionally, these findings were in line with a research by Popovi et al (21) that was done in Belgrade and found that three-quarters of the sample had a low QoL. According to the researcher, the majority of family caregivers struggle to control the sickness because they don't have enough information about it, which lowers their QoL.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the relationship between family caregivers overall knowledge scores and overall QOL scores regarding lymph node cancer, the current study found that there was a very significant positive connection between these two variables among the examined sample at P-value 0.001. These findings were in line with a research carried out in France by Popović et al (21) who found a highly significant positive association between total knowledge and total QOL related lymph node cancer among the sample they were studying. From the investigator point of view, the more knowledge of family caregivers increases their QoL.…”
Section: Discussionsupporting
confidence: 91%